Number theory arithmetic in Shangri-La proceedings of the 6th China-Japan seminar - Kanemitsu, Shigeru; Li, Hongze; Liu, Jianya (Mathematics professor) (Series on number theory and its applications, 2013)
This volume is based on the successful 6th China-Japan Seminar on Number Theory that was held in Shanghai Jiao Tong University in August 2011. It is a compilation of survey papers as well as original works by distinguished researchers in their respective fields. The topics range from traditional analytic number theory -- additive problems, divisor problems, Diophantine equations -- to elliptic curves and automorphic L-functions. It contains new developments in number theory and the topics complement the existing two volumes from the previous seminars which can be found in the same book series --